Modulation of Metabolome and Bacterial Community in Whole Crop Corn Silage by Inoculating Homofermentative Lactobacillus plantarum and Heterofermentative Lactobacillus buchneri - Xu, Dongmei; Ding, Wurong; Ke, Wencan; Li, Fuhou; Zhang, Ping; Guo, Xusheng (Frontiers in Microbiology, 2019)
The present study investigated the species level based microbial community and metabolome in corn silage inoculated with or without homofermentative Lactobacillus plantarum and heterofermentative Lactobacillus buchneri using the PacBio SMRT Sequencing and time-of-flight mass spectrometry (GC-TOF/MS). Chopped whole crop corn was treated with (1) deionized water (control), (2) Lactobacillus plantarum, or (3) Lactobacillus buchneri. The chopped whole crop corn was ensiled in vacuum-sealed polyethylene bags containing 300 g of fresh forge for 90 days, with three replicates for each treatment. The results showed that a total of 979 substances were detected, and 316 different metabolites were identified. Some metabolites with antimicrobial activity were detected in whole crop corn silage, such as catechol, 3-phenyllactic acid, 4-hydroxybenzoic acid, azelaic acid, 3,4-dihydroxybenzoic acid and 4-hydroxycinnamic acid. Catechol, pyrogallol and ferulic acid with antioxidant property, 4-hydroxybutyrate with nervine activity, and linoleic acid with cholesterol lowering effects, were detected in present study. In addition, a flavoring agent of myristic acid and a depression mitigation substance of phenylethylamine were also found in this study. Samples treated with inoculants presented more biofunctional metabolites of organic acids, amino acids and phenolic acids than untreated samples. The Lactobacillus species covered over 98% after ensiling, and were mainly comprised by the L. acetotolerans, L. silagei, L. parafarraginis, L. buchneri and L. odoratitofui. As compared to the control silage, inoculation of L. plantarum increased the relative abundances of L. acetotolerans, L. buchneri and L. parafarraginis, and a considerable decline in the proportion of L. silagei was observed; whereas an obvious decrease in L. acetotolerans and increases in L. odoratitofui and L. farciminis were observed in the L. buchneri inoculated silage. Therefore, inoculation of L. plantarum and L. buchneri regulated the microbial composition and metabolome of the corn silage with different behaviors. The present results indicated that profiling of silage microbiome and metabolome might improve our current understanding of the biological process underlying silage formation.